Lysine relay mechanism coordinates intermediate transfer in vitamin B6 biosynthesis - Rodrigues, Matthew; Windeisen, Volker; Guédez Rodríguez, Gabriela Liuvanova; Strohmeier, Marco; Sinning, Irmgard; Tews, Ivo (Nature chemical biology, 2017)
Substrate channeling has emerged as a common mechanism for enzymatic intermediate transfer. A conspicuous gap in knowledge concerns the use of covalent lysine imines in the transfer of carbonyl-group-containing intermediates, despite their wideuse in enzymatic catalysis. Here we show how imine chemistry operates in the transfer of covalent intermediates in pyridoxal 5′-phosphate biosynthesis by the Arabidopsis thaliana enzyme Pdx1. An initial ribose 5-phosphate lysine imine is converted to the chromophoric I320 intermediate, simultaneously bound to two lysine residues and partially vacating the active site, which creates space for glyceraldehyde 3-phosphate to bind. Crystal structures show how substrate binding, catalysis and shuttling are coupled to conformational changes around strand β6 of the Pdx1 (βα)8-barrel. The dual-specificity active site and imine relay mechanism for migration of carbonyl intermediates provide elegant solutions to the challenge of coordinating a complex sequence of reactions that follow a path of over 20 Å between substrate- and product-binding sites.